2016
DOI: 10.1016/j.jocn.2016.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in multiple sclerosis: gender matters

Abstract: Apathy has been recognized as a frequent symptom in multiple sclerosis (MS) but uncertainty remains about its prevalence and clinical correlates. Therefore, the objective of this work was to assess the prevalence of apathy in patients with MS and to identify clinical and demographic correlates. A case-control study with 30 patients and 30 healthy controls matched for age, gender and education was performed. Apathy diagnosis was established using Robert et al.'s criteria. Additionally, apathy was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
1
15
0
5
Order By: Relevance
“…Interestingly, when we examined whether the mediation effect of apathy was consistent across sex, we found that apathy mediated the effect of depression on cognitive control for women, and not for men, even though the difference between females and males failed to reach statistical significance in this sample. Studies in other clinical populations have found that while women have higher rates of depression overall, men are more likely to have depression with apathy than women, 17,18 and older age has also been observed to have higher correlation with apathy for men than women 32 . In this study, while severity of apathy present among men and women did not differ, apathy appeared to mediate cognitive control for women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, when we examined whether the mediation effect of apathy was consistent across sex, we found that apathy mediated the effect of depression on cognitive control for women, and not for men, even though the difference between females and males failed to reach statistical significance in this sample. Studies in other clinical populations have found that while women have higher rates of depression overall, men are more likely to have depression with apathy than women, 17,18 and older age has also been observed to have higher correlation with apathy for men than women 32 . In this study, while severity of apathy present among men and women did not differ, apathy appeared to mediate cognitive control for women.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the literature, we predicted that apathy would mediate memory and executive control difficulties in older adults with major depressive disorder. Further, we examined if apathy played a different role in male and female participants with late-life depression, as gender differences in apathy prevalence have been observed in other clinical samples such as Parkinson’s disease, 17 and multiple sclerosis 18 .…”
Section: Objectivementioning
confidence: 99%
“…There is conflicting evidence in the literature on the influence of sex on MS fatigue, with one study suggesting that cognitive fatigue is prevalent in males [61] another claiming fatigue to be sex invariant [62] and recent research showing, in line with our findings, that females are more prone to experience cognitive fatigue than males [63]. In our sample, sex influence was particularly evident in RRMS patients, whilst it tended to disappear in PMS, with a trend towards significance in the analysis of interaction with phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…9 Apathy is defined as a reduction or loss of motivation for behavioral, cognitive, and emotional activities. 10,11 In patients with MS, apathy occurs with a prevalence ranging from 20% to 50% 9,1215 and is associated with neurological disability, cognitive fatigue, and increased distress in caregivers. 12,15 Most often apathy has been described in comorbidity with depression in MS, but one recent study identified “pure apathy” in MS too, in association with executive dysfunctions, in particular with deficits of inhibitory control.…”
Section: Introductionmentioning
confidence: 99%